Role of insulin-like growth factor 1 (IGF1) in the regulation of mitochondrial bioenergetics in zebrafish oocytes: lessons from in vivo and in vitro investigations - Biswas, Subhasri; Ghosh, Soumyajyoti; Maitra, Sudipta (Frontiers in Cell and Developmental Biology, 2023)
Optimal mitochondrial functioning is indispensable for acquiring oocyte competence and meiotic maturation, whilst mitochondrial dysfunction may lead to diminished reproductive potential and impaired fertility. The role of the intra-ovarian IGF system in ovarian follicular dynamics has been implicated earlier. Although several studies have demonstrated the role of the IGF axis in facilitating mitochondrial function over a multitude of cell lines, its role in oocyte energy metabolism remains largely unexplored. Here using zebrafish, the relative importance of IGF1 in modulating oocyte mitochondrial bioenergetics has been investigated. A dramatic increase in ovarian lhcgr and igf1 expression accompanied heightened ATP levels and mitochondrial polarization in full-grown (FG) oocytes resuming meiotic maturation and ovulation in vivo. Concomitant with elevated igf1 expression and IGF1R phosphorylation, hCG (LH analog) stimulation of FG follicles in vitro prompted a sharp increase in NRF-1 and ATP levels, suggesting a positive influence of gonadotropin action on igf1 expression vis-à-vis oocyte bioenergetics. While recombinant IGF1 administration enhanced mitochondrial function, IGF1R immunodepletion or priming with PI3K inhibitor wortmannin could abrogate NRF-1 immunoreactivity, expression of respiratory chain subunits, ΔΨM, and ATP content. Mechanistically, activation of PI3K/Akt signaling in IGF1-treated follicles corroborated well with the rapid phosphorylation of GSK3β at Ser9 (inactive) followed by PGC-1β accumulation. While selective inhibition of GSK3β promoted PGC-1β, Akt inhibition could abrogate IGF1-induced p-GSK3β (Ser9) and PGC-1β immunoreactive protein indicating Akt-mediated GSK3β inactivation and PGC-1β stabilization. The IGF1-depleted follicles showed elevated superoxide anions, subdued steroidogenic potential, and attenuated G2-M1 transition. In summary, this study highlights the importance of IGF1 signaling in oocyte bioenergetics prior to resumption of meiosis.